PARENTS' PERSPECTIVES ON THE USE OF VERBAL ABUSE IN DISCIPLINING CHILDREN AGED 5-6 YEARS - Sartika, Dewi; Dhieni, Nurbiana; Yetti, Elindra (Universitas Panca Sakti Bekasi, 2025)
From an early age, it is important for parents to teach their children a disciplined lifestyle. In their role as the closest figures to the child, parents bear the responsibility of shaping discipline. Self-discipline is regarded as a valued asset for a child's development, as it can have positive effects throughout their adulthood. The practice of discipline can mold a child's personality to be more organized and strengthen their ability to regulate themselves. The implementation of discipline is often associated with punishment, which can lead to child abuse. Speaking of child abuse, one of the forms that is often overlooked and considered normal is verbal abuse. This study aims to describe parents’ perspectives on the use of verbal abuse in disciplining children aged 5-6 years. The type of research used is descriptive qualitative. The method used is a case study. The research location was at Cendekia Pasir Putih Kindergarten Depok, West Java. The research was conducted in May 2023. Data collection using interviews and documentation. Interviews were conducted in depth with six parents. The results showed that parents' understanding of non-violent discipline is still low. Parents tend to believe that discipline and stern reprimands are acceptable without considering the long-term impact on the child's development. The implementation of discipline sometimes still involves using harsh words toward the child.